2022
DOI: 10.3390/nu14245266
|View full text |Cite
|
Sign up to set email alerts
|

Alcoholic Liver Disease Is Associated with Elevated Plasma Levels of Novel Advanced Glycation End-Products: A Preliminary Study

Abstract: Elucidating the biochemical mechanisms associated with the progression of alcoholic liver disease (ALD) to more advanced stages such as alcoholic hepatitis (AH) remains an important clinical and scientific challenge. Several hypotheses point to the involvement of advanced glycation end-products (AGEs) in alcohol-associated liver injuries. Recently, we determined the structure of a synthetic, melibiose-derived AGE (MAGE), which was an analog of the novel AGE subgroup AGE10. The primary objective of our study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 68 publications
(90 reference statements)
0
4
0
Order By: Relevance
“…They investigated various generation conditions, such as the concentration of lysine, reaction time, and temperature, and found that CEL was generated at much higher proportions than CML under the same condition (CEL >> CML). Litwinowicz et al determined the structure of novel melibiose-derived AGEs (MAGE) and classified them as AGE-10 [ 63 ].…”
Section: Use Of the Novel In Vitro Assay To Assess The Effects Of Kam...mentioning
confidence: 99%
“…They investigated various generation conditions, such as the concentration of lysine, reaction time, and temperature, and found that CEL was generated at much higher proportions than CML under the same condition (CEL >> CML). Litwinowicz et al determined the structure of novel melibiose-derived AGEs (MAGE) and classified them as AGE-10 [ 63 ].…”
Section: Use Of the Novel In Vitro Assay To Assess The Effects Of Kam...mentioning
confidence: 99%
“…These AGEs can induce cytotoxicity, thereby including inflammation, because RAGE and TRL4 are expressed on the surfaces of various cells [ 1 , 11 , 26 ]. Furthermore, researchers have attempted to show that AGEs in the fluid correlate with the onset/progression of specific diseases, proving that AGEs could be biomarkers for these diseases [ 11 , 18 , 19 , 23 , 24 , 69 , 70 , 71 ]. The most beneficial and authentic biomarkers are (i) generated in specific organs and (ii) detected upon disease onset/progression, or organ dysfunction [ 72 , 73 , 74 , 75 ].…”
Section: Intra-/extracellular Ages and Lsrdsmentioning
confidence: 99%
“…Notably, Kato et al simultaneously analyzed four AGEs [CML, CEL, N δ -(5-hydro-5-methyl-4-imidazolone-2-yl)-ornithine (5-hydroxy-5-methylimidazolone) (MG-H1), and N ω -carboxymethyl-arginine (CMA)] in the serum of nephropathy patients using LC-ESI-MS and showed that MG-H1 dramatically increased relative to the other three AGEs [ 70 ]. Lirwinowicz et al determined the structure of a synthetic, melibiose-derived AGE (MAGE) and showed that MAGE in plasma correlated with NASH in a clinical study [ 71 ]. Although the structure of TAGE remains unclear, serum TAGE levels are associated with DM, CVD, NASH, infertility, cancer, and Alzheimer’s disease [ 5 ] and may be rare biomarkers with utility in determining the risk of various LSRDs.…”
Section: Intra-/extracellular Ages and Lsrdsmentioning
confidence: 99%
See 1 more Smart Citation